Gendered risks: access to and utilization of sexual and reproductive health services among young migrants in Southwestern Uganda: the role of the ‘lending a hand’ intervention - Kawuma, Rachel; Tumwesige, Edward; Asiimwe, Allen; Bernays, Sarah; Seeley, Janet (Frontiers in Reproductive Health, 2024)
Introduction Young migrants may engage in risky behaviours due to social, economic, and psychological challenges as they try to “get by” in their new host communities. This can result in unintended pregnancies, sexually transmitted infections including HIV, and poor mental health outcomes. During a study to test the feasibility and acceptability of an early intervention to reduce the harm of patterns of risk associated with migration, we assessed access to and utilization of sexual and reproductive health services (SRH) among recent migrants (14–24 years) in south-western Uganda. Methods The intervention conducted in 2022/23 involved training peer supporters to provide referral advice and support to young people. Between March–November 2022, 20 young migrants (11 males and 9 females) were purposively selected to participate in two in-depth interviews each to explore their experiences during the intervention. Data were analysed thematically. Results Women engaged in transactional sex to supplement their low pay while men got involved in risky behaviour once they had earned some money. Many suffered from sexually transmitted infections-related symptoms, were at risk for HIV infection and some women had fears of unwanted pregnancy. While some tried to seek for SRH services from public facilities, poor health service delivery such as long queues and shortages of drugs, discouraged them from going there. Young people tried to access treatment from private facilities but could not afford the costs. The intervention increased knowledge about SRH and supported young people to access services from the public health facilities at no cost thus increasing utilization. Conclusion Sexual health risks were experienced differently by women and men. The women were likely to experience symptoms related to sexually transmitted infections (including HIV) much earlier than men and this could increase their likelihood to engage with SRH services. The intervention served to increase men's readiness to access SRH services by providing them at a time and place that is convenient. Recognizing the different risk profiles of young people is important in tailoring appropriate interventions to promote equitable access and utilization of SRH services for both genders in this vulnerable population.